Analysis of Audience Acceptance of the Use of Regional Languages in YouTube Content Kebung “Misteri Pangkalan Bebay” - Afeby Ade Habibansyah (CV Projurnal Mitra Publikasi, 2025)
This study analyses the audience's reception of the use of regional languages in Kebung YouTube content entitled “Misteri Pangkalan Bebay”. The formulation of the problem in this study is to explore how the audience responds to the use of regional languages in the content. This study uses a qualitative method with Stuart Hall's reception analysis approach with 3 categories; 1) Dominant Hegemonic, 2) Negotiated Reading, 3) Oppositional Position. The research findings show that the majority of viewers receive the content positively and feel a sense of cultural closeness through regional languages. The implication is that the use of regional languages can increase social interaction and strengthen cultural identity in the digital space. This study provides insight for content creators and media researchers regarding the positive impact of using regional languages in digital content, encouraging the preservation and development of regional language wealth.